ISOLATED POSTERIOR CRUCIATE LIGAMENT TEAR: A RARE SPORTS RELATED INJURY - Idrees, Mohammad; Ahmad, Anwar (Journal of Ayub Medical College Abbottabad, 1998)
Isolated injury of the posterior cruciate ligament (PCL) of knees is an extremely uncommon occurrence. Majority of such injuries follow motor vehicle collision and sports associated accidents. Magnetic resonance imaging (MRI) is the most reliable and highly sensitive cross sectional imaging modality to confirm the diagnosis. The case under review emphasises the use of MRI in knee injuries involving ligaments and menisci.